A generalized non-isothermal tank model for liquid dominated geothermal reservoirs - Tureyen, Omer Inanc; Akyapı, Erinç (Elsevier BV, 2011)
We present a generalized non-isothermal tank model for predicting the pressure and temperature behaviors of liquid dominated geothermal reservoirs. A geothermal system is represented by a single or multiple tanks. These tanks can represent the reservoir, multiple reservoirs, aquifers or any other component of a geothermal system. The mass and energy balance equations for each tank are solved jointly. One of the main advantages of the model is that only a small number of tanks are used for modeling which avoids over parameterization of a geothermal system and results in faster run times when compared with fully discretized numerical simulators. Synthetic examples are used for studying the effects of heat conduction on reservoir performance, an analysis of the location of injection wells, recovery times of depleted geothermal fields and the benefits of using temperature data for a better characterization of the geothermal system.